SEJARAH PEMBANGUNAN BENTENG LIWU BURANGASI KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN PADA ABAD XVII - Rista Rista; Aswati M (Journal Idea of History, 2019)
The location of Buton at strategic cruise made its position vulnerable to external threats in the sultanate period. As the protective measure, the sultanate built the Liwu Burangasi Fortress in the XVII century. Therefore, this study focused to describe the history of the Liwu Burangasi Fortress. The problems in this study were: (1) how was the constraction background of the Liwu Burangasi Fortress, (2) how was the position of Liwu Burangasi Fortress in the defense structure of the Buton Sultanate, (3) What was the function of the Liwu Burangasi Fortress in the Buton Sultanate period. This study used historical method developed by Kuntowijiyo, namely (a) Topic Selection, which was done through emotional closeness and intellectual closeness, (b) Collection of sources, which was done through document studies, library research, interviews and observations, (c) Source verification, which was carried out through external criticism and internal criticism, (d) Source interpretation, which was carried out through analysis and synthesis, (e) historiography. The results of this study showed that (1) the history of the development of the Liwu Bungungasi Fortress was closely related to defense and security strategies. (2) The position of Liwu Burangasi Fortress in the structure of the Buton Sultanate wa as part of the community defense system that existed at the time of the Buton Sultanate. The Liwu Burangasi Fort with the Keraton Fortress could be seen in the structure of government, the political field, the economic field, the socio-cultural field, the field of defense and security, and the legal field. (3) The function of Liwu Burangasi Fortress during the Buton Sultanate had a dual function and role, namely as a defense and protection for native people and as a place of community settlement. Keyword: Development, Sultanate, Fortress, Defense, Protection